(untitled) (ЕтноАнтропоЗум, 2014)
The paper explores notions of “the rural” and “the urban” in modern Poland through examining the work of Teatr Wiejski Węgajty, a small theatre company in northern Poland and how this work highlights and provokes tensions between notions of ‘the rural’ and ‘the urban’ amongst those who participate and experience the theatre’s performances. The text explores how, by using various aspects of traditional village-based performance techniques the theatre attracts urban participants who seek contact with village culture, and how this contact may contrast sharply with the perceptions and views of rural inhabitants